2014
DOI: 10.1016/j.clinthera.2014.08.007
|View full text |Cite
|
Sign up to set email alerts
|

Cost-minimization Analysis of IgPro20, a Subcutaneous Immunoglobulin, in Japanese Patients With Primary Immunodeficiency

Abstract: Switching from IVIG to SCIG reduced markedly productivity loss and hospital-related absenteeism. The reduction in hospital visit frequency due to the use of home-based IgG therapy enabled by the change in administration route is expected to produce an important pharmacoeconomic benefit in Japan. Study Code: ZLB06_002CR, ClinicalTrials.gov identifier: NCT01199705.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
15
0
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 21 publications
(18 citation statements)
references
References 22 publications
2
15
0
1
Order By: Relevance
“…The Life Quality Index scores included areas such as treatment interferences with daily activities, treatment-related problems (such as convenience or painfulness of infusions), convenience of the setting in which the treatment was conducted, and costs of therapy and transportation to the location of therapy. Index scores for all domains were higher with SCIG than with IVIG [ 58 ].…”
Section: The Health-economic Impact Of High-volume Subcutaneous Biothmentioning
confidence: 99%
“…The Life Quality Index scores included areas such as treatment interferences with daily activities, treatment-related problems (such as convenience or painfulness of infusions), convenience of the setting in which the treatment was conducted, and costs of therapy and transportation to the location of therapy. Index scores for all domains were higher with SCIG than with IVIG [ 58 ].…”
Section: The Health-economic Impact Of High-volume Subcutaneous Biothmentioning
confidence: 99%
“…Moreover, studies from Germany and the United States revealed that moving from IVIG to SCIG administration will decrease 50% and 88% of costs, respectively ( 12 , 13 ). In addition, studies in Sweden, Japan, and France showed less costs in SCIG than IVIG method ( 14 - 16 ). This study aimed at determining the cost-effectiveness of SCIG delivery at home compared with IVIG administration at hospital for PI patients from the perspective of the Iranian health care system.…”
Section: Introductionmentioning
confidence: 99%
“…A recent review of 25 studies noted that 4 studies evaluating health economics in SCIG and IVIG therapy all found SCIG to be more cost effective, mainly through the reduction of lost work or school days [ 48 ]. Other studies have shown that SCIG is more cost effective due to issues with IVIG such as personnel required to administer, facility rooms, administrative overheads and productivity loss [ 42 , 49 , 50 ]. In comparison to patients on IVIG, patients on SCIG miss significantly fewer days of work or school [ 51 , 52 ] and one study also noted they spend significantly fewer days in the hospital [ 51 ].…”
Section: Introductionmentioning
confidence: 99%